Pathological Findings of Synchysis Scintillans Secondary to Familial Exudative Vitreoretinopathy With Chronic Exudative Retinal Detachment. (March 2020) - Lin, James; Garcia, Armando; Chen, Ying; Dubovy, Sander; Lee, Wendy; Kopplin, Laura J.; Berrocal, Audina
Purpose: We describe a unique case of synchysis scintillans in a 23-year-old woman with a history of chronic exudative retinal detachment in the setting of familial exudative vitreoretinopathy. Methods: Fundus and slit-lamp photographs were obtained at presentation, and pathological studies were performed on the enucleated specimen to confirm the diagnosis. Results: Synchysis scintillans is a degenerative condition of cholesterol deposition that affects severely damaged eyes, often as a result of chronic vitreous hemorrhage or retinal detachment. In this case, synchysis scintillans presented as crystals in the anterior chamber in the setting of a chronic retinal detachment. After enucleation, there were noted to be cholesterol slits on pathological correlation, confirming the diagnosis. Conclusions: This case demonstrates the importance of clinical pathological correlation in the diagnosis of synchysis scintillans migrating into the anterior chamber.